Measuring User Engagement in Mobile Classroom Response System: A Case Study - Tek, Yong Lim; Chia, Ying Khor; Yin, Bee Oon (Springer, Cham, 2017)
Mobile classroom response system, formerly known as clicker, is a promising technology to engage students in a lecture hall. Previous studies reported the positive effects of clickers on student engagement. However, most studies focused on patterns of cohort transitions using clickers during peer-instruction activities. This paper describes a mixed method approach to explore the dynamic of user engagement among undergraduate students in a local Malaysian university. Both interaction log and diary study were selected to track the pattern of ninety five registered students using mobile classroom response system across seven lecture weeks. Interaction logs were used to profile user type, participation type and submission type. The analysis of interaction logs revealed that seven visitors participated during lecture, only around 18% of registered students participated actively, registered students were more likely to answer all questions at the end of lecture compared to the beginning of lecture and middle of lecture. On the other hand, the analysis of diary entries provided qualitative information about user engagement attributes such focused attention, felt involvement, endurability, perceived usability and novelty. Both interaction log and students diary indicated that two registered students had positive engagement using mobile classroom response system during lecture.